ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI JUMLAH PENERIMAAN PAJAK PENGHASILAN ORANG PRIBADI (STUDI KASUS DI WILAYAH KERJA KANTOR PELAYANAN PAJAK BATU) - Dina W Fitriani; Putu Mahardika Adi Saputra (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2009)
The objective of this study is mainly to analyze factors that influence the amount ofpersonal income tax that collected by Batu tax service office in its work areas. Inorder to address the research questions, this paper utilizes the multiple regressionanalysis. Shortly, our findings conclude that the most dominant factor that influencesour dependent variable is the amount of registered taxpayers.Keywords: personal income tax, taxpayer, multiple regression analysis